Degrees of irreducible morphisms in generalized standard coherent almost cyclic components - Chaio, Claudia Alicia (2017)
We study the degrees of irreducible morphisms between indecomposablemodules lying in generalized standard coherent almost cyclic componentsof Auslander-Reiten quivers of artin algebras.